Effects of Biofertilizer and NPK Fertilizer to Increase the Growth of Tomato (Solanum lycopersicum) Planted In Fusarium oxysporum Infected Soils - Elizabeth Kaya; Diana Mailuhu; A Marthin Kalay; Abraham Talahaturuson; Anastasia T. Hartanti (Faculty of Agriculture, Pattimura University, 2020)
One of the tomato plants diseases is wilting due to Fusarium oxysporum attack. Biological control and management of soil fertility are efficient options. Efforts to increase soil fertility are using organic and inorganic fertilizers. This study aims to assess and obtain doses of sago ela compost added by Trichoderma and Azotobacter (KESTA) and organic liquid fertilizer (POC) or NPK to increase tomato plants growth on pathogen Fusarium oxysporium infected-soil both on nurseries and pots. The treatments tested were the dose of KESTA (K0 = Without KESTA, K1 = 15 tons of KESTA ha-1, K2 = 30 tons of KESTA ha-1, K3 = 45 tons of KESTA ha-1) and two types of fertilizers, namely: (P0 = Without Fertilizer, P1 = liquid organic fertilizer (POC) 10 mL L-1 P2 = NPK fertilizer 1,000 kg ha-1). This study was designed using a completely randomized design. The results showed that (1) the application of KESTA and fertilizers (POC and NPK) effects the wilt disease intensity, plant height, plant fresh and dry weight at the age of 28 days after planting; and the plant height at the age of 35 days after planting, (2) The most effective dose of KESTA is 45 tons ha-1, because it can reduce the intensity of withering up to 61.92%. Meanwhile, the types of NPK and POC fertilizers could reduce the intensity of the disease by 23.08% and 13.32%, respectively, (3) the application KESTA of 45 ton / ha is more effective if given with POC or NPK, as shown by the increasing in plant height, fresh and dry weight at the age of 28 days after planting in the nursery, and plant height at the age 35 days after planting in pot.